Pemenuhan Spiritual Pada Pasien Kanker : A Literature Review - Marti Husen; Iman Permana (Jurnal Keperawatan Muhammadiyah, 2021)
Background: Cancer treatment can not only focus on the quantity or physicality of the patient, but also pay attention to factors of quality of life, pain, stress, anxiety, fatigue, fear of death, and depression in patients who are often missed in the treatment of cancer patients. Spiritual needs are important needs to be met in patients with cancer in addition to other aspects of the need, because this disease can affect all aspects of the sufferer's life both physical, psychological and spiritual. Objective:this study aims to determine the spiritual fulfillment in cancer patients.  Method : This research is a literature review with the process of collecting data through 3 databases namely Pubmed , EBSCO and Proquest . Search Literature with the word key " Spiritual experience Spiritual meaning OR AND Cancer Patients" article published in the 5 years of the last is from the year 2015 to 2019 with the criteria of inclusion Results: The literature search results found 169,139 journals, Pubmed found 583, Ebsco 12,582, Proquest 155,974, the entire database was categorized with inclusion criteria and only 14 articles met the criteria. Conclusion: spiritual fulfillment can improve the quality of life of cancer patients, by increasing spiritual aspects can provide peace, comfort for cancer patients. So the importance of spiritual needs in health care.